2020
DOI: 10.3389/fphar.2020.570616
|View full text |Cite
|
Sign up to set email alerts
|

Phytocannabinoids Profile in Medicinal Cannabis Oils: The Impact of Plant Varieties and Preparation Methods

Abstract: Cannabis (Cannabis sativa L.) is a highly promising medicinal plant with well-documented effectiveness and growing use in the treatment of various medical conditions. Cannabis oils are mostly used in galenic preparations, due to their easy adjustment of the administration dose, together with the enhanced bioavailability of its active compounds. As stated by the Italian Law (9/11/2015, 279 Official Gazette), “to ensure the quality of the oil-based cannabis preparation, the titration of the active substance(s) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…A further area to be explored is the potential interaction at T-type I Ca between Cannabis terpenoids and the phytocannabinoids examined here, as terpenoids alone also modulate these channels (El Alaoui et al, 2017;Gadotti et al, 2021). Cas et al, 2020;Suraev et al, 2018). However, defining the activities of naturally low abundance phytocannabinoids compounds at human T-type I Ca will contribute to a more complete understanding of their actions in more complex systems and is an essential part of understanding the pharmacology of Cannabis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A further area to be explored is the potential interaction at T-type I Ca between Cannabis terpenoids and the phytocannabinoids examined here, as terpenoids alone also modulate these channels (El Alaoui et al, 2017;Gadotti et al, 2021). Cas et al, 2020;Suraev et al, 2018). However, defining the activities of naturally low abundance phytocannabinoids compounds at human T-type I Ca will contribute to a more complete understanding of their actions in more complex systems and is an essential part of understanding the pharmacology of Cannabis.…”
Section: Discussionmentioning
confidence: 99%
“…This present study shows that phytocannabinoids, alone or in combination, have the potential to exert therapeutic effects on diseases associated with aberrant T‐type I Ca activity, without the unwanted psychotropic effects associated with THC‐dominant medicinal cannabis. Several studies have demonstrated anticonvulsant effects of cannabis extract preparations (Hussain et al, 2015; Tzadok et al, 2016), but recent studies, including a survey showing the composition and use of unregulated cannabis extracts in the treatment of childhood epilepsy in the Australian community, indicate a significant variability in the minor phytocannabinoid content, making correlation between specific cannabinoid content and effectiveness difficult (Dei Cas et al, 2020; Suraev et al, 2018). However, defining the activities of naturally low abundance phytocannabinoids compounds at human T‐type I Ca will contribute to a more complete understanding of their actions in more complex systems and is an essential part of understanding the pharmacology of Cannabis .…”
Section: Discussionmentioning
confidence: 99%
“…10 The bioavailability of plant material itself is lower in comparison because conversion of tetrahydrocannabinolic acid (THCA) to its neutral counterpart THC must occur in order to have psychoactive effects. 4 During the drying of cannabis, THCA is converted to THC. 19 It was surprising that THCA was not detected in the jenny’s plasma following exposure to the fresh, undried plant material (Table 1).…”
Section: Casementioning
confidence: 99%
“…This variability stems from the application of differing operating protocols during the preparation phase, but also because of the natural variability of Cannabis inflorescences. To minimise the former factor, it is to be hoped that there will soon be a standard production protocol for Cannabis extracts [ 5 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%